Synovial mast cells and osteoarthritis: Current understandings and future perspectives - Guanghui Hao; Shanqian Han; Zhangang Xiao; Jing Shen; Yueshui Zhao; Qi Hao (Heliyon)
Osteoarthritis (OA) is a prevalent joint disease worldwide that significantly impacts the quality of life of individuals, particularly those in middle-aged and elderly populations. OA was initially considered as non-inflammatory arthritis, but recent studies have identified a substantial number of immune responses in OA, leading to the recognition of inflammation as a key factor in its pathogenesis. An increasing number of studies have found that mast cell (MC) and MC-secreted inflammatory mediators and cytokines are notably increased in the synovial fluid of OA patients, indicating a potential association between MCs and the onset and progression of synovial inflammation. The present review aims to summarize the significance and mechanism of MCs in the pathogenesis of OA. Meanwhile, we also discuss the clinical potential of using MCs as therapeutic target for OA therapy. Modulating the activities of MCs or the mediators of MCs in the synovial fluid inflammatory microenvironment will be promising new options for the treatment of OA.